ANALISIS YURIDIS NORMATIF DAN HUKUM ISLAM TERHADAP PUTUSAN MAHKAMAH KONSTITUSI NOMOR 30- 74/PUU-XII/2014 TENTANG BATAS USIA PERKAWINAN ANAK (PEREMPUAN) ABDUL HADI DAN HASANAIN HAIKAL - Hasanain Haikal (Program Studi Hukum Keluarga Islam, 2016)
Age criteria in marriage law which sets the age limit for 16 years women is disputed by the applicant judicial review to the Constitutional Court (MK) through case No. 30 and 74 / PUU-XII /2014 on Age Limits on Marriage Children (Women), then it must be raised to be 18 years old. The applicant considers that the marriage law contrary to the Constitution (Constitution) 1945, which is